COMPARATIVE STUDY OF DIFFERENT COIL GEOMETRIES FOR WIRELESS POWER TRANSFER USING PROTOTYPES - SUHAIRY, MUHAMMAD SHAZWAN (Universiti Teknologi PETRONAS, 2016)
Wireless power transfer (WPT) is widely used in the consumer market. As the technology growth, the demand in WPT has become more popular. As for this project, inductive resonance wireless power transfer is used to transfer the power. Its working principal is by using magnetic resonance to transfer the power from transmitting coil to receiving coil. Application that is widely used nowadays is in phone charging. However, the main problem is on the design of coil geometries which have contribute in different strength of magnetic field. Thus, this project is focus on analysing and comparing the performance of various shapes of coil geometries. In this project, prototype will be used from the previous final year project (FYP) student’s prototype. In addition, the respective shapes of coil that is used for the project is circular planar coils, square planar coils and pentagon planar coils. All coil will be compared based on its performance and findings on the literature review. Last but not least, the expected end-result for this project is pentagon planar coils to produce the highest efficiency followed by circular and square planar coils.